Tradução comentada para o português dos contos "Berenice" e "Ligeia" de Edgar Allan Poe - Melo, Jinnye Altamira de Paiva (2021)
This work presents a commented translation into Brazilian Portuguese of the short stories “Berenice” and “Ligeia” by the writer Edgar Allan Poe (1809 1849). In the first chapters, I present a brief study about the author and his aesthetic literary perspect ive , before proceeding to an analysis of the selected short stories. To discuss the structure of the short story and the importance of Poe for the genre, I turn to theorists such as Cortázar (1993) and Todorov ( Then I present the translated stories and a reflection on my translation process. Theorists like Berman (2008) with his question of the translation “ethical, poetic and thinking”, and Vermeer (2014) with the theory of skopos helped to build the theoretical basis of the comments. In these comme nts, I tried to consider the particularities of Poe's writing while composing the main character's language. The elements commented on were alliterations, assonances, neologisms, hyperba tons , hyperbolic language, and punctuation.